2006
DOI: 10.1152/ajpheart.00066.2006
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of whole blood to the control of plasma asymmetrical dimethylarginine

Abstract: The endogenous nitric oxide (NO) synthase (NOS) inhibitor asymmetrical dimethylarginine (ADMA) is elevated in many patients and may contribute to the initiation and progression of their disease. While some mechanistic pathways have been identified, tissue-specific contributions to ADMA control remain unclear. We sought to determine if whole blood (WB) could participate in ADMA control ex vivo. Anesthetized male Sprague-Dawley rats underwent exsanguinations, and WB preparations were incubated at 37°C for 5 h. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 60 publications
6
40
0
Order By: Relevance
“…However, given the strong link we previously described between ADMA and proteinuria in nondiabetic stage 1 CKD patients (20), this methylarginine may be a likely mediator of the Hb-proteinuria interaction as related to FMD. This possibility is in line with the hypothesis that red blood cells may participate in the regulation of the NO system by modulating ADMA levels (22). To convert total cholesterol in mg/dl to mmol/L, multiply by 0.02586; Hb in g/dl into mmol/L, multiply by 10.…”
Section: Discussionsupporting
confidence: 74%
“…However, given the strong link we previously described between ADMA and proteinuria in nondiabetic stage 1 CKD patients (20), this methylarginine may be a likely mediator of the Hb-proteinuria interaction as related to FMD. This possibility is in line with the hypothesis that red blood cells may participate in the regulation of the NO system by modulating ADMA levels (22). To convert total cholesterol in mg/dl to mmol/L, multiply by 0.02586; Hb in g/dl into mmol/L, multiply by 10.…”
Section: Discussionsupporting
confidence: 74%
“…29 Recent studies measuring intracellular levels of ADMA in red blood cells showed that they are at 40.61Ϯ7.15 mol/L. 30 Importantly, a 5-fold increase in methylarginine concentration has been shown in endothelial cells when they were exposed to methylarginines added to the culture medium. 31 This level of methylarginines is probably attributable to the arginine transport system referred to as the Yϩ transporter.…”
Section: Discussionmentioning
confidence: 99%
“…both theoretical and actual toxicology in the context of in vitro human and whole animal models. Such substances include: c scavengers of nitric oxide (NO) and inhibitors of NO generation that may result in lack of vascular relaxation (eg, hemoglobin, both free and in microparticles, 14 alterations in RBCs themselves, 15 and asymmetric dimethylarginine that may inhibit NO synthase 16,17 In some cases, the biological effects of stored/aged blood in whole animal models has resulted in profound pathology and pathophysiology, with substantial morbidity and mortality of recipients of the stored (but not fresh) units of blood.…”
mentioning
confidence: 99%